2006
DOI: 10.1016/j.joca.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of intra-articular caspase inhibition therapy following osteochondral injury

Abstract: Intra-articular administration of the caspase inhibitor Z-VAD-fmk effectively blocks chondrocyte PCD following experimental osteochondral injury in this model. Inhibition of chondrocyte PCD rescues chondrocytes that would otherwise die, limiting subsequent cartilage loss. To our knowledge, this study is the first to demonstrate that short-term inhibition of chondrocyte PCD leads to long-term preservation of cartilage in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Furthermore, shear strain is exaggerated in degenerative cartilage samples (32). Also of interest are reports that administering pancaspase inhibitors to experimental OA models resulted in fewer cartilage lesions by preventing cell death (8,36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, shear strain is exaggerated in degenerative cartilage samples (32). Also of interest are reports that administering pancaspase inhibitors to experimental OA models resulted in fewer cartilage lesions by preventing cell death (8,36).…”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 Interestingly, recent studies have shown that short-term intra-articular administration of a potent caspase inhibitor (Z-VAD-FMK, ZVF) results in a decrease in chondrocyte apoptosis and subsequently less cartilage degeneration after experimental osteochondral injury in rabbits. 14 Further, the use of apoptosis inhibitors in vivo reduced the number of cells undergoing apoptosis in cartilage that had been prepared for surgery, leading to the conclusions that cell death inhibitors could improve the results of cartilage repair surgery. 15 In the light of these findings, we hypothesized that inhibition of the cell death that occurs as a response to wounding of articular cartilage will result in enhanced cartilage integrative repair.…”
Section: Introductionmentioning
confidence: 99%
“…While the benefits of apoptosis inhibition have been demonstrated in animal models of degenerative arthritis, cartilage injury, and cartilage repair using marrow-stimulation techniques [13,17,40], the in vivo effects of apoptosis inhibition in the setting of osteochondral allograft transplantation have not been reported. Based upon existing research, beneficial effects would be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of different stimuli initiate chondrocyte apoptosis [2,3,6,9,10,23,24,26,30,32], a universal feature of chondrocyte apoptosis is caspase activation [13,16,17,31,35,39,44] (Fig. 1).…”
Section: Chondrocyte Apoptosis Regulation Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation